Prulink Syariah Products at PT Prusyariah Binjai Agency Achievement in Islamic Shari'a Review - Sri Putri Wahyundari; Tri Inda Fadhila Rahma (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The development of the Islamic insurance industry is not balanced with the amount of research that will halal the Islamic insurance product. This indicates that there are still many inconsistencies in Islamic insurance products with Islamic principles. The application of a sharia insurance product is very important to maintain the halal product. In this paper, we will discuss the mechanism for applying prudential sharia insurance products (pru link sharia). By systematically describing the application of Islamic prinkets which will then be compared with the principles of Islam. This research shows that Prudential Shariainks are not fully in accordance with sharia principles.